Analysis of energy and exergy use for process heating in the industrial sector of Malaysia - Saidur, Rahman; Khaliq, A.H.A.; Masjuki, Haji Hassan (International Journal of Exergy, 2006)
In this paper, the useful concept of energy and exergy utilisation is defined, analysed and applied to the industrial sector of Malaysia (i.e. food, textiles, woods, papers, chemicals, non-metallic, base-metal, fabricated metal and miscellaneous) for heating processes by taking into account the energy and exergy flows for the period from 1988 to 1998. The energy and exergy efficiencies are determined for the sub sectors and devices used in each sub-sectors. Energy and exergy flow diagrams for the overall efficiencies of Malaysian industrial sector are also illustrated in this paper. It is found that the current methodology applied in Saudi Arabia is suitable for the analysis of energy and exergy use in the Malaysian industrial sector. In Malaysia, the industrial sector utilises more than half of the total energy generated, and so it is very crucial to identify the energy flows in this sector and draw up the exergy losses.